ECOLOGICAL READING ON SELECTED AYURZANA AND YONG SHU HOONG’s POEMS - Indriyanto, Kristiawan (Lire Journal (Journal of Linguistics and Literature), 2018)
This paper explores how nature is depicted by two poets of different nationality using ecocriticism. Ecological approach is used as framework to focus more on the connection and relationship between human and their environment and the possible impact on the disruption of human-nature relationship. People living in different environment will have different reception toward their surroundings. The aim of this paper is to explore how both poets describe nature in their selected works. Ayurzana and Yong ShuHoong represent two poets exposed to different environment;hence, this paper seeks to present how different Ayurzana who lives in a rural area portray his surrounding compared with Hoong as an urban dweller. As a native Mongolian, Ayurzana explores the close connection between Mongolian people and nature. On the other hand, Hoong’s poetry elaborates life in cities and people that become detached from the natural environment. By analyzing two poets from different living conditions, this paper acknowledges that ecological issue might differ from one region to another.